Pengaruh Disiplin Kerja dan Locus of Control Terhadap Prestasi Kerja dan Kepuasan Kerja sebagai Variabel Intervening pada Kantor Bupati Pasaman Barat - Riani Pratiwi; Ramdani Bayu Putra; Vicky Brahma Kumbara; Hasmaymelis Fitri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the effect of work discipline and locus of control on work performance and job satisfaction as intervening variables at the West Pasaman Regent's office. The data analysis method used is multiple linear regression analysis. By circulating the questionnaire as many as 59 respondents. The results obtained were that there was a positive and significant impact between work discipline on job satisfaction in employees of the West Pasaman Regent's Office. There is a positive and significant impact between locus of control on job satisfaction in West Pasaman Regent Office employees. There is a positive and significant impact between work discipline on work performance for employees of the West Pasaman Regent's Office. There is a positive and insignificant impact between locus of control on work performance in West Pasaman Regent Office employees. There is a positive and significant impact between job satisfaction on work performance for employees of the West Pasaman Regent's Office. There is a positive and insignificant impact of work discipline on work performance through job satisfaction in employees of the West Pasaman Regent's Office. Job satisfaction has not been able to mediate the effect of work discipline on work performance. There is a positive and significant impact of locus of control on work performance through job satisfaction. Job satisfaction can mediate the influence of locus of control on work performance